The Influences of Digital Technology, Digital Literacy, and Digital Marketing On The Performance of SMEs in Bekasi - Harry Patria; M. Arfani Fatchul Alam; Agus Mulyadi; Ardhi Setyarko (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This research aimed to determine the influences of digital technology, digital literacy, and the use of digital marketing on the performance of small and medium enterprises (SMEs) in Bekasi, West Java. The study is quantitative research with a survey method. Study data were collected using a questionnaire technique with a sample of 338 respondents through convenience and snowball sampling. The SPSS software version 25.0 was used to analyze the research data. To ascertain the effects of independent variables on dependent variable, multiple regression analysis was used. This study has limitations, such as data collection was only limited in Bekasi area and the sampling was conducted without dividing the sector or business type of SMEs. Future studies in other areas with distinctive characteristics or in other parts of the world by using other methods such as random sampling by dividing SMEs based on business sector are potential to increase the model's validity and reliability. The findings of this study demonstrate that the use of digital technology, digital literacy, and digital marketing all significantly and favorably affect the performance of SMEs, with the usage of digital marketing having the most impact. By emphasizing the advancement of digital technology, employee digital literacy, and the use of digital marketing to enhance performance and maintain sustainable growth, the study's findings also offer SMEs improvement strategies.